The Educational Philosophy of Traditional Pesantren Roudlotul Muhsinin Al-Maqbul: Integrating Future Education Values - Sulton, Ahmad; Sirait, Sangkot; Arif, Mahmud (Cendekia: Kependidikan dan Kemasyarakatan, 2022)
This study explores why Pesantren al-Maqbul maintains a traditional education system from educational philosophy. This research was qualitative. These research findings are: (1) the reason Pesantren al-Maqbul still insists on maintaining the traditional education system cannot be separated from the construction of its educational philosophy; (2) the influence of the educational ontology basis of the Pesantren al-Maqbul on its educational goals can be identified from the tendency of monism which places Allah's revelation in the form of Al-Qur'an Hadith as the only authoritative source of knowledge; (3) the influence of the educational epistemological foundation of Pesantren al-Maqbul on its educational goals can be seen from Bayani's tendencies in its epistemology; (4) the influence of the axiological basis (values) on the educational goals of the Pesantren al-Maqbul can be seen from the tendency of Irfani's reasoning, which is visible in the Pesantren al-Maqbul.